Freedom - Gray, Tim. author. aut Link
IX, 191 p.
Keywords: Part of a series aimed at introducing readers to the intricacies of contemporary debates concerning fundamental political issues. Aiming to offer a comprehensive account of freedom, this work explores the issues of aggregation and distribution, justification, measurement and meaning.